Hybrid method of fuzzy homotopy and runge kutta fehlberg method for solving fuzzy nonlinear equations / Nurul Jannah binti Mohd Aisa - Nurul Jannah Mohd Aisa (Institute of Engineering Mathematics, Universiti Malaysia Perlis, 2018)
The objectives of this study are ; to solve fuzzy nonlinear equations using the FHRKFM method ; to estimate the accuracy and convergence of FHRKFM for solving fuzzy nonlinear equations ; to compare the performance of FHRKFM in term of error with the Fuzzy Homotopy and Euler method (FHEM) and Fuzzy Homotopy and Runge Kutta of Order Four method (FHRK4M).